2007
DOI: 10.1007/s00464-007-9459-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic live donor nephrectomy for right kidneys: Experience in a German community hospital

Abstract: Laparoscopic donor nephrectomy is a safe procedure and has been established as the method of choice for live kidney donation in our clinic. Laparoscopic procurement of right and left kidneys can be performed with comparable quality and outcome for donors and recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…While a few authors have demonstrated that complex right renal vascular anatomy is not a contraindication to RLDN, others have suggested modification such as the use of saphenous vein patch for renal vein reconstruction and the use of the retroperitoneoscopic approach for obtaining maximum arterial length. [1718192021] As some studies have demonstrated that RLDN is faster, with quicker convalescence, shorter OR time and lesser blood loss, RLDN has to be encouraged to extend the advantages of minimally invasive surgery to a greater donor pool. [222324]…”
Section: Discussionmentioning
confidence: 99%
“…While a few authors have demonstrated that complex right renal vascular anatomy is not a contraindication to RLDN, others have suggested modification such as the use of saphenous vein patch for renal vein reconstruction and the use of the retroperitoneoscopic approach for obtaining maximum arterial length. [1718192021] As some studies have demonstrated that RLDN is faster, with quicker convalescence, shorter OR time and lesser blood loss, RLDN has to be encouraged to extend the advantages of minimally invasive surgery to a greater donor pool. [222324]…”
Section: Discussionmentioning
confidence: 99%
“…There are previous studies reporting no differences in the complication rates in terms of laterality. 8,9 We also found that complication rates were similar in donors who underwent left-and right-sided HALDNs except spleen injuries.…”
Section: Commentmentioning
confidence: 70%
“…7 Several recent studies have reported that the right donor kidney is not associated with an increased risk of complications. 8,9 Meanwhile, right donor nephrectomy is frequently performed using open surgery owing to the technical difficulties associated with laparoscopic nephrectomy.…”
mentioning
confidence: 99%
“…The current approach is to use whichever side is better for the donor followed by the side that is better for the recipient. 15 A recent meta-analysis showed no differences in kidney function and thrombosis when they compared the right versus the left kidney. 16 We decided to use the right kidney in 3 cases, 2 because the left kidney had 4 arteries and the other case because the donor had underwent previous surgery for diverticular disease in the sigmoid colon, so we suspected adhesions at that level.…”
Section: Discussionmentioning
confidence: 99%